The Role Of Competitive Advantage Towards Accelerating Internationalization Of SMES In Indonesia - Gunartin, Gunartin; Mukhlis, Imam; Danardana Murwani, Fulgentius (International Journal of Educational Research & Social Sciences, 2022)
This paper aims to explore the role of competitive advantage in accelerating the internationalization ofSMEs in Indonesia. The source of this paper is secondary data with a literature and empirical study approach from previous articles and other supporting sources. Data sources and various articles show that digitalization as a competitive advantage has a very important role in accelerating the internationalization of SMEs in Indonesia, but the results of the study of various sources of digitizing strategies for competitive advantage, many factors determine the international acceleration of SMEs in Indonesia such as partnerships, customer relations, business process management, as well as investing in information and communication resources. The government's role is also very dominant in the process towards accelerating the internationalization of SMEs in Indonesia